Survival Book to Help BIPA Learners Off the Hook of Culture Shock - Hespi Septiana; Him’mawan Adi Nugroho; Warsita Noer Ardiyanti; Masilva Raynox Mael; Agus Ridwan (Faculty of Humanities, Universitas Jenderal Soedirman, 2021)
From time to time, Indonesian for Foreign Speakers (BIPA) continues to grow, including BIPA at the State University of Surabaya (Unesa). It cannot be denied that in its journey, BIPA Unesa encountered various problems. One of them is a report from a foreign student who was confused when he first arrived in Surabaya. Their confusion includes finding the ideal place to live, using online motorcycle taxi applications, and using public facilities such as markets, hospitals, and police stations. Not only that, but the understanding of academic rules on campus has also not been able to be conveyed on target. Some local students and lecturers have helped, but the limited number and time have made it impossible to assist students. Therefore, this research focuses on making a pocketbook called